2002
DOI: 10.1099/0022-1317-83-10-2543
|View full text |Cite
|
Sign up to set email alerts
|

Selection of antigenic variants in maedi–visna virus infection

Abstract: In order to analyse the pattern of sequence variation in maedi-visna virus (MVV) in persistently infected sheep and to answer the question of whether antigenic variants are selected in a long-term MVV infection, an 87 bp variable region in the env gene of ten antigenic variants and 24 nonvariants was sequenced. Nine of the ten antigenic variants had mutations in this region, comprising 24 point mutations and a deletion of 3 bp. Twenty-three of the point mutations (96 %) were nonsynonymous. There was only a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Previous works have estimated the evolution rates of SRLVs in animals infected over the long term (1,12). In light of these results, the large genetic distance observed between the sequence of clone PBMC12-25 in goat 12 and that of clone PBMC13-12 in goat 13 from both cluster I (28.2 and 26%) and cluster II (13.9 and 24.9%) sequences could hardly be attributed to the evolution of these viruses within their hosts.…”
Section: Discussionmentioning
confidence: 79%
“…Previous works have estimated the evolution rates of SRLVs in animals infected over the long term (1,12). In light of these results, the large genetic distance observed between the sequence of clone PBMC12-25 in goat 12 and that of clone PBMC13-12 in goat 13 from both cluster I (28.2 and 26%) and cluster II (13.9 and 24.9%) sequences could hardly be attributed to the evolution of these viruses within their hosts.…”
Section: Discussionmentioning
confidence: 79%
“…In the last case, host may have evolved to mount an effective long-lasting restriction mechanism of lentiviral replication in vivo. Neutralizing antibodies were detected in ELISA positive sera from red deer however, they unlikely play an important role in the viral infection restrictive pathway as described in caprine and ovine species [ 21 , 50 ]. Serological reaction was mostly detected by home-made ELISA in comparison with commercial tests as described for ovine and caprine infections likely due to the inclusion of novel epitopes providing wider cross-reactivity [ 39 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the variants usually do not replace the original infecting strain of virus, and the antigenic drift does not appear to be necessary for either virus persistence or development of CNS or lung lesions [292,391]. A recent study, however, showed that there is selection for mutants that escape neutralization [394]. Most viral proteins can act as antigens for CTL, although only epitopes in POL have been characterized in detail [331].…”
Section: Role Of Viral Antigenic and Strain Variation In Diseasementioning
confidence: 97%